Exploring the involvement of serine proteases in neutrophil extracellular traps: a review of mechanisms and implications - Aleksandra Korba-Mikołajczyk; Katarzyna Dominika Służalska; Paulina Kasperkiewicz (Cell Death and Disease)
Abstract Neutrophils play a critical role in the first-line of defense against circulating pathogens and contain a wide array of granules that store antimicrobial proteins, with neutrophil serine proteases (NSPs) and defensins serving as crucial components. NSPs such as neutrophil elastase (NE), proteinase 3 (PR3), cathepsin G (CatG) and neutrophil serine protease 4 (NSP4) exhibit distinct substrate specificities that underpin their critical roles in immune defense and inflammation [1]. After neutrophils are activated, they form and release neutrophil extracellular traps (NETs) consisting of decondensed chromatin and intracellular proteins through a process called NETosis, which leads to neutrophil death. Although NETosis is predominantly categorized as a suicidal process, several studies have suggested that neutrophils remain viable after NETosis under certain circumstances. To date, research has focused on the mechanisms underlying NETosis and roles of various factors such as reactive oxygen species (ROS), nicotinamide adenine dinucleotide phosphate (NADPH), myeloperoxidase (MPO), and peptidyl arginine deiminase 4 (PAD4). Metabolic pathways such as glycolysis are critical for NET formation, with exogenous glucose and glutamine enhancing NET release. Neutrophils cultured in glucose-free conditions fail to undergo NETosis upon phorbol-12-myristate-13-acetate (PMA) stimulation. ROS-mediated signaling promotes NE release from the azurosome, F-actin degradation, and NE translocation to the nucleus, facilitating chromatin decondensation. Notably, rapid F-actin disassembly has similarly been observed during NETosis induced by PMA and ionomycin. Recently, the role of NSPs during NET formation and their extracellular functions have received increased attention from researchers. The exact mechanism of NET formation remains unknown, and the process itself still raises controversies regarding its overlapping aspects with other forms of cell death, the role of NSPs, the nature of scaffolding DNA, and the possible involvement of other factors. Here, we discuss the intricate pathways governing NET formation, outline the diverse enzymes and proteins crucial for NET assembly, and highlight potential mechanisms controlling NET release. We pay particular attention to the regulation of NSP proteolytic activity and the nuanced role of NSPs during processes such as degranulation, which can be classified as extracellular mechanisms associated with NET formation. Dysregulated NETosis and NSP activity have been implicated in pathological states and diseases. Therefore, understanding the functions of NSPs and their role in NET formation might facilitate the development of new diagnostic and therapeutic strategies.